2008
DOI: 10.1063/1.2948856
|View full text |Cite
|
Sign up to set email alerts
|

Electrical detection of photoinduced spins both at room temperature and in remanence

Abstract: We demonstrate a photodetector with ferromagnetic contacts which can electrically detect the polarization degree of incoming light using spin filtering of photoinduced spin-polarized electron currents. Our structure is a pin diode with a single GaAs quantum well as active region and a Fe∕Tb multilayer on top of a MgO tunnel barrier as n-contact where the spin-polarized electron current is filtered. The photocurrent depends on the magnetization of the contacts and on the polarization of the injected light. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…This time-resolved analysis shows that our experimental procedure controls the polarization of the VCSEL output by the spin-polarized excitation as concluded earlier from time-integrated measurements. 16 The frequency of oscillations does not depend on excitation conditions within the experimental accuracy. Accordingly, emission of only one circular polarization as it may be desired for applications cannot be easily achieved with the control parameters available in the present setup ͑see below͒.…”
Section: -15mentioning
confidence: 99%
See 3 more Smart Citations
“…This time-resolved analysis shows that our experimental procedure controls the polarization of the VCSEL output by the spin-polarized excitation as concluded earlier from time-integrated measurements. 16 The frequency of oscillations does not depend on excitation conditions within the experimental accuracy. Accordingly, emission of only one circular polarization as it may be desired for applications cannot be easily achieved with the control parameters available in the present setup ͑see below͒.…”
Section: -15mentioning
confidence: 99%
“…In a recent letter, we studied the time-integrated polarization degree of commercial electrically pumped VCSELs and showed that even dominantly electrically pumped devices can show spin dynamics with additional spin-polarized optical excitation. 16 In this letter we present a time-resolved analysis of the complex polarization dynamics of spinpolarized VCSELs close to threshold and discuss ultrafast modulation scenarios in future spin-VCSELs. 17,18 Since no electrically pumped room-temperature spin-VCSEL device is available yet, we chose a hybrid excitation scheme.…”
Section: -15mentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive understanding of the interplay between the spin excited emission and cavity anisotropies as birefringence and dichroism of the devices is necessary in order to develop efficient spin-VCSELs 11,12 . Upon cw excitation we have demonstrated that the linear polarization predetermination can be suppressed with spin polarized injection 13,14 . For the practical application, the temporal spin dynamics is of primary interest, so a comprehensive understanding of the complex interplay of spin dynamics, carrier density, photon density and devices parameters is highly desirable.…”
Section: Introductionmentioning
confidence: 97%